The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3390/ijerph15122779
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition Analysis of Factors Affecting Changes in Industrial Wastewater Emission Intensity in China: Based on a SSBM-GMI Approach

Abstract: This paper investigated the factors driving the changes in industrial wastewater emission intensity (IWEI) across provinces in China. To do this, we proposed a Super-efficiency Slacks-based Measure-Global Malmquist Index (SSBM-GMI) to decompose the change in IWEI into the effects from efficiency change (ECE), technological change (TCE), capital–wastewater substitution (KWE) and labor–wastewater substitution (LWE). The method was applied to conduct an empirical study using Chinese provincial data from 2003–2015… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 64 publications
1
3
0
Order By: Relevance
“…The coefficients for FDI are negative but not significant in the YRDUA, suggesting that FDI has not promoted the growth in eco-efficiency in this region. This result is similar to Wen [29], who suggested that the impacts of FDI on total productivity differed by region in China. The reason may be that foreign investment mainly focused on manufacturing, consequently bringing about tremendous pressure on the resources and environment in the YRDUA.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The coefficients for FDI are negative but not significant in the YRDUA, suggesting that FDI has not promoted the growth in eco-efficiency in this region. This result is similar to Wen [29], who suggested that the impacts of FDI on total productivity differed by region in China. The reason may be that foreign investment mainly focused on manufacturing, consequently bringing about tremendous pressure on the resources and environment in the YRDUA.…”
Section: Resultssupporting
confidence: 89%
“…Thus, the PPS of the global frontier is given by:PPSGlb = {PPS1 PPS2 PPST} where PPSGlb denotes the specific technologies of the global frontier (i.e., best practice frontier) [29]. The production technology is assumed to follow all the standard axioms of production theory, including the assumptions of bounded set, bounded convexity, etc.…”
Section: Methodology and Datamentioning
confidence: 99%
“…Only Beijing, Shanghai and Gansu showed strong decoupling in this time period. The finding that Beijing and Shanghai experienced strong decoupling in the 10th FYP is not surprising, as they were the very few regions in China with advanced technology and equipment (Chen et al, 2016;Wu et al, 2018a), optimized industrial structure (Geng et al, 2014) and preferable environmental policies (Cheng et al, 2018;Chen et al, 2019). However, for the less developed inland province, Gansu, it may be due to that its Zhangye City was selected as the first pilot city for building Water-saving Society in 2002, which helps improve water use efficiency and reduce wastewater discharges of Gansu.…”
Section: Decoupling Analysismentioning
confidence: 99%
“…8 It is necessary to promote the implementation of water-saving policies and coordinate the relationship between the subsystems. 9 Shortages of capital and labor reduced the IWD intensity of cities in the middle of the Yellow River, 10 and urban wastewater posed an ecological burden to the Bohai Sea. 11 Economic factors are the main factors affecting IWD in all provinces, and the logarithmic mean divisia index method is normally used to evaluate the spatiotemporal characteristics and driving forces of IWD in China.…”
Section: ■ Introductionmentioning
confidence: 99%